Modern evolution and hydrological regime of the Bashkara Glacier Lakes system (Central Caucasus, Russia) after the outburst on September 1, 2017 - Ekaterina D. Pavlyukevich; Inna N. Krylenko; Ivan V. Krylenko (Russian Geographical Society, 2025)
In high mountain areas, glacial lake outbursts are often the cause of floods and extreme events. Investigation of these events is especially important in the context of ongoing intensive deglaciation and climate change. This study is focused on the monitoring of the Bashkara Glacier Lakes after their outburst on September 1st, 2017, which are located in the most glaciated and populated part of the Central Caucasus of Russia, in the Mt. Elbrus region. Following the incident, the lakes system has transformed into flow-through. However, the lakes system has undergone significant changes and remains unstable and potentially hazardous. In this research, we used remote sensing data and field observations to assess the condition of the Bashkara Lakes. The water level, area and volume of the lakes are unstable. Between 2018 and 2024, the area of Bashkara Lake increased by 32% and volume by 41%, with the level increasing by 3.2 meters. At the same time, Lapa Lake was rapidly shrinking. The area of Lapa Lake in 2018-2024 decreased by 51%, the volume by 66%, and the level decreased by 4.2 meters. In addition to the continuing rise of the water level, the possibility of future rockfalls cannot be excluded, which can trigger a re-outburst. Ephemeral glacier lakes were also discovered, their merging with the main lake can cause a dramatic increase in the lake volume. On the other hand, other factors, such as the decrease in water temperature of Bashkara lake and its flowage, indicate the stability of the lakes system.